Patient's Coping of Anxiety Level of Dialysis Patients - Kristia Lulu Sabrina; Mori Agustina br Perangin-Angin (Jurnal Keperawatan Silampari, 2023)
This study aims to determine the effect of coping with anxiety levels. The research method used is descriptive correlative using Cross-Sectional. The results showed moderate anxiety levels in the hemodialysis installation at Advent Bandung Hospital with 86 people (96.63%). In conclusion, coping mechanisms influence the patient's anxiety levels. Keywords: Anxiety, Dialysis, Patient Coping